2022
DOI: 10.36941/ajis-2022-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage of Perceived CSR, Corporate Reputation, Organizational Commitment, and Purchase Intention

Abstract: The ongoing pandemic has resulted in various parties being affected both economically and socially. This makes social issues become very sensitive. For companies, efforts that can be made to help deal with the pandemic while improving performance are CSR (corporate social responsibility). Some literature proves the positive influence of CSR on company reputation, organizational commitment, and purchase intention. Therefore, this study aims to analyze the relationship between perceived CSR to company reputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…This study fills this gap. Moreover, this research findings also resonate with studies on topics like CSR and financial performance, and reputation [ [22] , [23] , [24] , [25] ], further revealing the pivotal role of investor attention in this relationship. This provides more detailed insights for market participants and decision-makers.…”
Section: Empirical Results and Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…This study fills this gap. Moreover, this research findings also resonate with studies on topics like CSR and financial performance, and reputation [ [22] , [23] , [24] , [25] ], further revealing the pivotal role of investor attention in this relationship. This provides more detailed insights for market participants and decision-makers.…”
Section: Empirical Results and Analysissupporting
confidence: 81%
“…Some academic research suggests that the two concepts have overlapping meanings [ 21 ]. For instance, a study within Indonesia's cement industry discovered that a company's perception of CSR significantly influences its reputation, organizational commitment, and consumers' purchase intentions [ 22 ]. Similarly, research from Serbia also validated the positive correlation between CSR and corporate reputation [ 23 ].…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%
“…Additionally, signaling theory suggests that brand reputation communicates details about the inherent intangible features of products such as quality, especially in the absence of alternative methods of assessment. Consequently, brand reputation may have an immediate impact on customer behavioral intentions (Jufri et al, 2022). Multiple studies have confirmed the impact of brand reputation on purchase intention.…”
Section: The Relationship Between Brand Reputation and Purchase Inten...mentioning
confidence: 99%